ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI PENONTON PENGGUNA APLIKASI TIKET BIOSKOP ONLINE - Ujang Asmara; Abdullah Risqillah; dwi ridho aulianto (UNIVERSITAS STEKOM, 2020)
Abstract The development of information and communication technology makes all things we need is more practical and easy. For example, ordering or booking ticket for cinema through an application. It is an example of the application of technology that is used to attract the number of buyers by service providers. The easy access on getting product or item is the desire of every consumer. The entry of technology changes the patterns of consumer behaviour from manual to digital or online. The service provider of online cinema ticket provides some features which can attract and will be the important thing for some buyers. The changing of ticket sales through application will definitely change ticket sales figures. This study aims to determine the factors which influence audience buying interest through the online cinema ticket application. The method used is a qualitative method with a case study approach. Data collection is done through interviews with viewers who use the online ticket booth application in buying tickets in the mall jatinangor town square. The results showed several factors that influence the interest in buying tickets using the application, namely time efficiency, promos and discounts, the latest films available (coming soon), the opportunity to get bigger tickets, can determine the choice of seats, avoid the queue, easy to use in transactions.